The effects of treatment with pimavanserin on activities of daily living in patients with Parkinson’s disease psychosis: a 16-week, single-arm, open-label study - Virgilio G. H. Evidente; Daryl DeKarske; Bruce Coate; Victor Abler (Therapeutic Advances in Neurological Disorders, 2024)
Background: More than half of patients with Parkinson’s disease will experience psychosis symptoms in the form of hallucinations or delusions at some point over the course of their disease. These symptoms can significantly impact patients’ health-related quality of life, cognitive abilities, and activities of daily living (ADLs) and function. Clinical assessment of how psychosis impacts these measures is crucial; however, few studies have assessed this sufficiently, in part due to a lack of appropriate scales for comprehensively assessing function. Objective: The objective was to assess how symptoms of Parkinson’s disease psychosis (PDP) impact ADLs and function, cognitive function, and health-related quality of life. Design: To address this unmet need, we utilized a modified version of the Functional Status Questionnaire (mFSQ) to measure the impact of psychosis on ADLs and function in patients with PDP treated with pimavanserin, a US Food and Drug Administration-approved medication to treat hallucinations and delusions associated with PDP. Methods: Eligible patients entered a 16-week, single-arm, open-label study of oral pimavanserin (34 mg) taken once daily. The primary endpoint was change from baseline to Week 16 on the mFSQ. Secondary endpoints included the Movement Disorders Society–modified Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) I and II; Schwab and England ADL; Clinical Global Impression–Severity of Illness (CGI-S), Clinical Global Impression–Improvement (CGI-I), and Patient Global Impression–Improvement (PGI-I), and were also measured as change from baseline to Week 16 using mixed-effects model for repeated measures (MMRM) and least-squares mean (LSM). Results: Our results in a proof-of-concept, 16-week, open-label clinical study in 29 patients demonstrated that an improvement in psychosis symptoms following treatment with pimavanserin was associated with improvements in multiple measures of ADLs and function. Notably, a significant improvement was found on the primary endpoint, change from baseline to Week 16 in mFSQ score [LSM [SE] 14.0 [2.50], n  = 17; 95% CI (8.8, 19.3); p  < 0.0001]. Conclusion: These findings highlight the potential for improvement in function with improvement of psychosis symptoms in patients with PDP and suggest that the mFSQ may be a measurement tool to evaluate the level of improvement in function. Trial registration: ClinicalTrials.gov Identifier: NCT04292223.